Multimedia Aided Language Teaching: An Ideal Pedagogy in the English Language Teaching of Bangladesh - Ahmed, Md. Kawser (American International Journal of Social Science Research, 2018)
Teaching English language around the globe is not only concentrated on grammars, series of writings and face to face interviews through conventional style but also centralized on the modern equipment, information and technology. Day to day updated accessories have made a tremendous progress in the pedagogy of English and ensured maximum benefits and acceptability among teachers and learners simultaneously. Observing the global usability and frequency, English language has appeared as a technology-but not as a language only but also as a channel of communication and language teaching. Application of multimedia in teaching-learning of English has earned best appreciation at any level of education and students have found English as an easy means of communication, conversation and interact with teachers with the blessing of multimedia and updated materials of language teaching. On the contrary, it is pitiful to observe that unavailability of modern accessories and elements in teaching English shows the namesake picture of multimedia used in third world countries especially in Bangladesh. This paper will focus on the significant progresses in the application of multimedia; take up of class with the aid of modern equipment and practical scenario of the use of multimedia in schools, colleges and universities of Bangladesh where multimedia based classroom is getting popular between teachers and students equally.